2013
DOI: 10.1016/j.neubiorev.2013.08.003
|View full text |Cite
|
Sign up to set email alerts
|

Into the groove: Can rhythm influence Parkinson's disease?

Abstract: Previous research has noted that music can improve gait in several pathological conditions, including Parkinson's disease, Huntington's disease and stroke. Current research into auditory-motor interactions and the neural bases of musical rhythm perception has provided important insights for developing potential movement therapies. Specifically, neuroimaging studies show that rhythm perception activates structures within key motor networks, such as premotor and supplementary motor areas, basal ganglia and the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
252
0
9

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 256 publications
(281 citation statements)
references
References 84 publications
11
252
0
9
Order By: Relevance
“…Rehabilitative approaches, such as Neurologic Music Therapy (NMT) [42] refer to neuroscientific models and use primarily the potential of musical stimuli to activate perception and production areas in the human brain, providing a series of therapeutic applications to sensory, cognitive, and motor dysfunctions resulting from neurological disorders. Using directive approach based on a series of exercises, NMT may be used, for example, to improve gait and movements in post-stroke and PD patients [43][44][45][46][47] and language in persons with aphasia [48,49] . On the other hand, simple music listening interventions don't require neither a specifically trained therapist nor a direct therapeutic relationship with the patient being that beneficial effects are induced by the content of the musical stimuli and by the activity of listening itself.…”
Section: Music Therapymentioning
confidence: 99%
“…Rehabilitative approaches, such as Neurologic Music Therapy (NMT) [42] refer to neuroscientific models and use primarily the potential of musical stimuli to activate perception and production areas in the human brain, providing a series of therapeutic applications to sensory, cognitive, and motor dysfunctions resulting from neurological disorders. Using directive approach based on a series of exercises, NMT may be used, for example, to improve gait and movements in post-stroke and PD patients [43][44][45][46][47] and language in persons with aphasia [48,49] . On the other hand, simple music listening interventions don't require neither a specifically trained therapist nor a direct therapeutic relationship with the patient being that beneficial effects are induced by the content of the musical stimuli and by the activity of listening itself.…”
Section: Music Therapymentioning
confidence: 99%
“…26,27 Because of these qualities, when used as an intervention for individuals with motor impairments, dance may contribute to improved HRQOL for individuals with PD. 28,29 Dance's effects upon HRQOL have been studied in other populations. A randomized controlled trial (RCT) of 162 adult participants who suffered from stress, demonstrated that dance/movement therapy was effective at improving short-and long-term HRQOL, as measured by the World Health Organization QOL questionnaire, compared with usual care.…”
Section: Does Increased Social Engagement and Better Motor Function Imentioning
confidence: 99%
“…Auditory cueing can improve gait in PD patients (Nombela et al, 2013;Bloem et al, 2015). Benoit et al extended this finding by determining whether auditory-cued gait training with music can facilitate both motor and perceptual timing in PD patients.…”
Section: Music Rhythm and Movementmentioning
confidence: 99%
“…During the last decade, there has been increasing interest and progress in adopting music as a therapeutic tool in neurological rehabilitation, and many novel music-based methods have been developed to improve motor, cognitive, language, emotional, and social deficits in persons suffering from a debilitating neurological illness, ranging from childhood and adolescence [e.g., autism (Geretsegger et al, 2014), dyslexia (Flaugnacco et al, 2015)] to adulthood and old age [e.g., stroke (Särkämö et al, 2008;Bradt et al, 2010;Rodríguez-Fornells et al, 2012;Altenmüller and Schlaug, 2015), Parkinson's disease (Nombela et al, 2013;Bloem et al, 2015), and dementia (Vink et al, 2011;Baird and Samson, 2015)]. Traditionally, the fields of music neuroscience and music therapy have progressed independently, providing separate lines of evidence for how music is processed in the healthy brain and how it can be used therapeutically.…”
mentioning
confidence: 99%